Inovasi Pembuatan Probiotik dari Limbah Pengolahan Ikan Jambal Roti - Herry; Tri Wahyuni; Eka Wijayanti; Kusuma Arumsari; Nusaibah (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
The production of salted jambal roti produces the main product in the form of salted fish fillets and by-products in the form of fish entrails. this byproduct is usually discarded and a problem in the environment. Therefore, this study aims to utilize these by-products to be made probiotics which are then used to increase fish production. The research method used was the experimental method with three treatments with doses of jambal fish contents 5%, 10% and 15%. The test parameters used included the quality test of probiotic bacteria and probiotic applications in catfish. From the results of the study obtained non-pathogenic bacteria content, Lactobacillus sp. and Bacillus sp. The abundance of probiotic bacteria in each treatment was around 105 CFU / ml according to the standard bacterial content in commercial probiotics. The probiotic application in catfish produces survival (SR) at a dose of 5%; 10%; 15 of 90%; 93%; 95% and feed efficiency (FCR) of 0.92; 0.90; 0.82. The best results are shown in the use of a 15% probiotic by producing a lower FCR and a higher SR.